Malaria: a retrospective study in Hospital Tengku Ampuan Rahimah (HTAR), Klang, Selangor, Malaysia (2004-2006) - Jamaiah, I.; Rohela, M.; Nissapatorn, V.; Amriana, A.; Sumaiyah, M.N.; Lila, M.; Norzawati, A. (SEAMEO Regional Tropical Medicine and Public Health Network, 2007)
This retrospective study was carried out to determine the prevalence of malaria among patients admitted to Hospital Tengku Ampuan Rahimah, Klang, Malaysia, from January 2004 to May 2006. A total of 37 malaria cases were analyzed. Most cases occurred among foreigners, 81 (30 cases), while Malaysians constituted 19 (7 cases). Among foreigners, Indians constituted the majority, 40.5 (15 cases). Among Malaysians, most cases occurred among Malays, 16 (6 cases), followed by Indians, 3 (1 case). Males, 89 (33 cases), were more commonly affected. The majority of cases were within the 20-39 year age group (84). Most cases occurred among laborers (24). Two species of malaria parasites were reported, of which Plasmodium vivax constituted the most, 70 (26 cases), followed by Plasmodium falciparum, 30 (11 cases). In this study, 40.5 (15 cases) developed chloroquine resistance: six cases of P. falciparum, and nine cases of P. vivax. The most common complications were thrombocytopenia, 65 (24 cases), and anemia, 54 (20 cases), followed by jaundice, 32 (12 cases), and hepatosplenomegaly, 22 (8 cases). There were no reported deaths. This new source of malaria coming from foreigners must be given serious attention, as it has great potential of increasing malaria cases in urban Malaysia.